2018
DOI: 10.5897/ajpp2018.4912
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat in patients with hyperuricemia and severe chronic kidney disease

Abstract: Febuxostat is a non-purine, selective inhibitor of both isoforms of xanthine oxido-reductase (XOR).Its pharmacokinetics is not dependent on renal clearance, and it may be advantageous in patients with chronic kidney disease (CKD). Although febuxostat is effective in patients with mild-to-moderate CKD, its efficacy and safety in patients with severe CKD remain unclear. This retrospective study included patients with an estimated glomerular filtration rate (eGFR) of < 30 ml/min/1.73 m 2 and hyperuricemia, who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…10 But, no difference of eGFR after 12 weeks therapy in CKD stage 4 and 5. 15 In our study, we found significant improvement of eGFR after one month and it continued till the end of study period. However, subgroup analysis had shown the significant increment of eGFR only in CKD stage 3 and 4 and insignificant increment in CKD stage 5.…”
Section: Discussionsupporting
confidence: 68%
“…10 But, no difference of eGFR after 12 weeks therapy in CKD stage 4 and 5. 15 In our study, we found significant improvement of eGFR after one month and it continued till the end of study period. However, subgroup analysis had shown the significant increment of eGFR only in CKD stage 3 and 4 and insignificant increment in CKD stage 5.…”
Section: Discussionsupporting
confidence: 68%